(untitled) (Scientific journal of the Fergana State University, 2025)
This article focuses on research results aimed at improving students’ physical and psychological development through the introduction of rhythmic gymnastics into the school physical education system. It examines the integration of this type of gymnastics into physical education activities using modern pedagogical methods and technologies, as well as analyzes its impact on students’ health and level of interest.